Undergraduate Students' Perspectives on Primary Care - Jessica A. Gold; Frances K. Barg; Katherine Margo (SAGE Publishing, 2014)
Background and Objectives: Despite the need for more primary care physicians, the number of medical students choosing primary care careers remains lower than other specialties. While undergraduate premedical education is an essential component in the development of future physicians, little is known about undergraduate students' perspectives on becoming primary care physicians. To better understand the early factors in career selection, we asked premed and former premed students their perceptions of primary care. Methods: Open-ended, semistructured interviews were conducted with 58 undergraduate students who represented three different groups: those who were currently premed and science majors, those who were nonscience majors and were currently premed, and those who were formerly premed. Specifically, we asked, "Why do you think there is a shortage of people who go into primary care?" Results: Undergraduates cited financial reasons, lack of "glamour," and the career being "uninteresting." Many believed that primary care lacked prestige, and others felt it had a negative stigma attached. Most had never even considered a career in primary care. A number of students also misunderstood what a career in primary care actually entailed. Conclusions: As early as freshman year in college, undergraduate students harbor misconceptions and negative opinions about primary care. Many of those who express interest in such a career seem to drop out of the premedical program. It is important to consider the early onset of these attitudes and a way to target this interested population when trying to address the shortage of primary care physicians.